Effects of air relative humidity on spectral characteristics of dielectric barrier discharge plasma assisted combustion reactor. (May 2020) - Deng, Jun; He, Liming; Zhao, Bingbing; Chen, Qiang
Abstract: Using dielectric barrier discharge (DBD), a cylinder plasma assisted combustion (PAC) reactor was designed and applied to real aero-engines. Through the acquired optical emission spectroscopy (OES), the effects of air relative humidity (RH) on important active products (e.g. excited nitrogen molecules and hydroxyl radical) of this reactor discharges were investigated. In addition, vibrational temperature of N 2 * was calculated by Boltzmann plots. The OES of OH radials at 309 nm was analyzed. The results indicated that most OES of second positive system (SPS) N 2 * (C Π 3 u → B Π 3 g ) had lower intensity at higher RH. The OES of first negative system (FNS) N 2 + (391.4 nm) enhanced at 25 50% RH and reduced at 50 95%. Vibrational temperature of N 2 * reduced with the increased RH. When RH was lower than 35%, the OES of OH( A ∑ 2 → X Π 2 ) decreased with the increase of RH. While RH was higher than 35%, OH intensity increased. These research results could provide a vital basis for further studying the effects of DBD PAC reactor on combustion performances of aero-engines. Highlights: A cylinder DBD plasma assisted combustion reactor for real aero-engines was designed. The optical emission spectroscopy of this reactor discharges was gained and analyzed under different air humidity. Vibration temperature of N 2 * was calculated by Boltzmann plots in different air relative humidity. The spectral intensity of main active products of this reactor discharges were analyzed in different air humidity.